Zgodovinski razvoj vodnih žag - Cimperšek, Mitja (Gozdarski vestnik, 2014)
Historical development of water mills in Slovenia is insufficiently investigated and often wrongly explained. The newest researches in Italy and Germany classified their typology and enabled us to determine emergence and development of water mills also on our territory. Friulian workers had indisputably brought the Venetian mill type %Venetian sawmill% to us already in the 14th century and despite their obsolescence large numbers of them survived until the second half of the 20th century. Socialistic society was not conducive to private business, so water wheels of the majority of mills came to a halt in a short period. Unfortunately, the few preserved ones are poorly protected as the rare monuments of our technical culture.
Keywords: lesna industrija; žagarstvo; vodne žage; venecijanke